Writing a statement. Issue 4 (2nd April 2020) - Peate, Ian
Abstract : This article considers the importance of statement writing. It will outline some of the reasons why the healthcare assistant and assistant practitioner (HCA and AP), the trainee/student/nursing associate (NA) may be required to write a statement. The article describes the various types of statement.